Parvovirus Infection: An Immunohistochemical Study Using Fetal and Placental Tissue. (January 2015) - Li, Jing Jing; Henwood, Tony; Van Hal, Sebastian; Charlton, Amanda
Parvovirus B19 infection causes 5% to 15% of cases of nonimmune hydrops fetalis. The aim of our study was to evaluate the use of immunohistochemistry in diagnosing parvovirus infection in fetal and placental tissue during routine fetal and perinatal autopsies. Histology slides of 20 cases of confirmed parvovirus infection were reviewed, and immunohistochemistry was applied to selected blocks of fetal and placental tissue. Immunohistochemistry was positive in all 20 cases, and histologic viral inclusions were seen in 19 cases. Immunohistochemical staining was closely correlated with histology and was more sensitive than histology in detecting virally infected cells, especially in autolyzed tissue. All cases also had confirmatory evidence of parvovirus infection by polymerase chain reaction of fetal liver and positive maternal serology, where it was available. We conclude that parvovirus immunohistochemistry is a reliable method for diagnosing parvovirus infection, especially in autolyzed tissue where histologic assessment may be suboptimal.